Developing a High Touch Model for Misconduct Processes - Lavallee, Suzie; Gadhia, Atul (Canadian Perspectives on Academic Integrity, 2021)
Using principles of restorative justice and best practices, we developed a new administrative model for misconduct procedures, with some significant success in reducing recidivism and increasing awareness amongst faculty and students. Key aspects included low barriers for instructors to report issues and semi-scripted student interviews for each offense. Though this 'high touch' model may not be fully scalable to all academic units, the interviewing process was particularly effective at identifying issues with student well being and academic struggles, allowing us to put students in touch with additional resources. We were also able to identify issues with instructions to students on exams and mistakes by instructors, which we used to inform faculty and prevent possible future harm to students. For these reasons, we advocate for a high touch approach to misconduct at an early stage of reporting.